An inertia measurement apparatus - Wong, Shaw Voon; Radin Sohadi, Radin Umar; Megat Ahmad, Megat Mohamad Hamdan; Tan, Kean Sheng (2014)
An apparatus 1 includes a static supporting structure 2, and a dynamic functional unit 3. The dynamic functional unit 3 generally includes a shaft system 23 and a plurality of arms 24. The static supporting structure 2 generally includes a pair of main frames. The pair of main frames includes a first main frame 4 and a second main frame 5 respectively constitute an upright rectangular frame that are formed by fastening four members of channel structural steel 6, 7, 8, 9; and 10, 11, 12, 13. The frames 4, 5 are separated at a distance and are connected via I-beam 14 at the mid span of the top horizontal members 9 and 13 of the main frames. To provide lateral stability to the overall supporting structure of the apparatus 1, the frames are also connected to each other at both lateral sides respectively by a pair of cross-connected equal-leg angle steel members 15, 16 and 17, 18.